Integrating Islamic Values into Indonesian Language Teaching Materials: Enhancing Learning Outcomes for 2nd Grade MI Students - Hilda Wahyuni; Fakhintan Ilza Karengga; Wilda Al Aluf; Muhammad Nasir; Yuliana Izdihar Firdaus; M. Zubad Nurul Yaqin (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aimed to develop Indonesian language teaching materials infused with Islamic values for second-grade students at Madrasah Ibtidaiyah (MI). The need for integrated character education within language learning underpins this research. The ADDIE development model—comprising analysis, design, development, implementation, and evaluation stages—guided the material creation process. Validation by material, media, and language experts resulted in an average score of 92.43%, indicating very high validity. The materials were implemented at MI Al-Hidayah, Malang Regency, involving 30 second-grade students. Practicality testing yielded a score of 90.19%, while learning outcomes improved significantly, with an 85.34% success rate. The materials incorporate Islamic values such as anger control, patience, gratitude, cleanliness, self-protection, and respect for parents, supported by engaging visual elements. These findings demonstrate that the developed materials are highly valid, practical, and effective in enhancing language skills and character education. This study contributes to holistic learning approaches aligned with the independent curriculum. Future research is recommended to expand the integration of Islamic values into other subjects to further support character-building in primary education.